Konseling Sebagai Metode Pemulihan PTSD Pada Anak Korban Pelecehan Seksual - Farsya Khairani Adi Ramadhan; Ati Kusmawati; Ilma Husnul Khotimah; Nirmala Fakhira Khansa (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research discusses counseling as a method of PTSD recovery in child victims of sexual abuse. Post Traumatic Stress Disorder (PTSD) is a psychological disorder that arises as a result of a traumatic event experienced or witnessed by an individual, which creates a sense of helplessness, resulting in serious disruption to one's quality of life. Recently, the phenomenon of sexual harassment has become increasingly rampant in society. Perpetrators are not only targeting adult victims, but also children. Sexual abuse experienced by a person can trigger the birth of PTSD. Victims of sexual abuse in children will cause physical and psychological trauma where psychological trauma will be heavier than physical trauma because it affects their social life. Significant psychological impacts, such as difficulties with various traumatic experiences, stigmatization, and even the potential risk of harmful behaviors such as self-mutilation or the tendency to become a perpetrator of sexual abuse in the future. Therefore, this issue needs to be addressed with behavioral counseling. This counseling assists children in learning to change problematic behaviors into applicable rules and norms. The purpose of counseling is to solve the client's problems or increase their strength to cope with life. This research uses a library research method, which is a method of collecting data by studying theories from various relevant literature.